Decentralization, disaster response, and administrative conjunction the case of selected municipalities in Albay and Sorsogon - Marcoleta, Rodante D. 1953-; Brillantes,Alex B.,Jr. (Quezon City National College of Public Administration and Governance, University of the Philippines Diliman, 2020)
This study delves into some important concepts in public administration: decentralization and disaster response. Apparently, there is still more in exploring their relationship, more particularly the impact of one on the other. This study aimed to determine any correlation between decentralization and disaster response in the selected LGUs in Albay and Sorsogon. Guided by an array of related literature and dissertations, the study sought to: (i) determine whether decentralization has influenced the execution of disaster response in the studied areas, (ii) identify the factors which enabled or impeded the adaptation of a disaster response, and (iii) determine the ways in which administrative conjunction manifested itself in the governance of disaster response. The types or forms of decentralization were proxied by the same core elements/ indicators that characterize good governance which, on their own, acted as similar variables that dictate the way disaster response was conformally administered. With the use of said indicators, the degree of decentralization in the studied area was analyzed on the basis of the respondents' feedback on the conditions that characterize the way they understood decentralization, and the lack of it, between two periods (1990-2017). The study found correlative effects of decentralization relative to the governance of disaster response, aided by the forms of administrative conjunction. While it was beyond this study to quantify the degree of disaster response, it was validated that the same dovetailed with LGU's extent of decentralization
Thesis (Doctor of Public Administration)--University of the Philippines Diliman
Keywords: Emergency management -- Philippines; Hazard mitigation -- Philippines -- Albay; Hazard mitigation -- Philippines -- Sorsogon; Decentralization in government -- Philippines